The Mystery of a Surname: On the Poetonym Dunchil in the Novel The Master and Margarita - Anatoly Arkadyevich Fomin (Вопросы ономастики)
This article examines the surname Dunchil’, which belongs to a minor character in Mikhail Bulgakov’s novel The Master and Margarita. The study concludes that the name is of occasional and authorial origin and proposes a hypothesis regarding its derivation. According to the suggested etymology, the anthroponym Dunchil is an anagram of the surname of one of the central characters in Aleksandr Ostrovsky’s comedy The Last Victim — Vadim Grigor’evich Dulchin. The anagram results from the metathesis of the final consonants in the two closed syllables of the surname Dul’chin, thus Dul’chin becomes Dunchil’. This rearrangement significantly alters the morphological form of the surname, making it sound strange, unusual, and atypical for the Russian anthroponymic system. Based on this etymology, the article argues for the importance of the intertextual function of the poetonym Dunchil’, which signals the embedding of another literary world within Bulgakov’s novel. From this perspective, the character may be viewed as a literary projection of Ostrovsky’s protagonist. A comparative analysis of the two characters reveals several notable similarities. First, both are involved in close relationships with women who play significant roles in their lives. Second, both are publicly exposed for deceiving those with whom they are romantically or domestically involved. Third, both disguise their true selves through deception. Fourth, once their fraud is uncovered, both receive their just punishment. Fifth, in both cases, it is a woman close to them who triggers their downfall unexpectedly for the character. Additional narrative details discussed in the article further support the proposed etymology of the surname Dunchil’.